Analysis from avian visual perspective reveals plumage colour differences among females of capuchino seedeaters (Sporophila) - Benites, Maria del Pilar (2010)
Females of the closely related capuchino seedeaters are difficult to distinguish from one another based on human visual perception of colouration and morphology. We examined plumage colour differences among females of four species, the tawny-bellied seedeater Sporophila hypoxantha, the dark-throated seedeater S. ruficollis, the rufous-rumped seedeater S. hypochroma, and the chesnut-bellied seedeater S. cinnamomea. Reflectance values were measured on museum skins, and interspecific differences were analyzed using the Vorobyev-Osorio avian colour discrimination model. Interspecific distances in the colour space calculated by the model were considerably higher than the threshold for colour discrimination, indicating the presence of colour differences among species that should be detectable by birds. Colour differences between S. hypoxantha and the other three species were the largest. A Discriminant Function Analysis showed that UV-wavelength was particularly important in species separation. Our results indicate that female plumage of these four species is considerably divergent in colour; these differences being imperceptible to the human eye, thus representing previously unknown morphological evolution in these species.